2010
DOI: 10.1378/chest.09-2644
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Avian Influenza A(H5N1) in Patients at the Persahabatan Hospital, Jakarta, Indonesia, 2005–2008

Abstract: Early diagnosis and effective treatment of human influenza A(H5N1) infection remains challenging. Most patients were referred late with advanced disease. Oseltamivir had limited clinical impact. Elevated D-dimer levels, consistent with fibrinolysis, and hyperglycemia warrant more research to determine their underlying mechanisms and optimal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 41 publications
1
20
1
3
Order By: Relevance
“…Increased serum ferritin levels have been observed in some viral infections such as hepatitis C (13), H5N1 (14) and dengue fever (15); however, very high levels, as observed in our patients, are not a known feature of common viral infections. High serum ferritin levels are a feature of HLH.…”
Section: Discussioncontrasting
confidence: 56%
“…Increased serum ferritin levels have been observed in some viral infections such as hepatitis C (13), H5N1 (14) and dengue fever (15); however, very high levels, as observed in our patients, are not a known feature of common viral infections. High serum ferritin levels are a feature of HLH.…”
Section: Discussioncontrasting
confidence: 56%
“…This is probably due to dysregulated systemic inflammatory responses, which lead to poor clinical outcomes [3537]. In our cohort, we observed that the rs4644 AA genotype was associated with the lower serum glucose levels, but no differences in serum leukocyte counts and CRP levels, both indicators for inflammation severity.…”
Section: Discussionmentioning
confidence: 59%
“…Consistently, Keller et al showed an activation of the fibrinolytic system during non-pathogenic IAV infection in mice [15]. Remarkably, in humans increased production of D-dimer, a marker of fibrinolysis was found to be a risk factor for fatal outcome of H5N1 and pandemic H1N1 virus infections [24], [25]. Furthermore, IAV infections have been associated with bleeding medical disorders [26], [27].…”
Section: Discussionmentioning
confidence: 79%